The birds of Irgiz & Turgay wetlands (Eurasian Journal of Ecology, 2016)
Lakes of the lower Irgiz & Turgay in the territory Irgiz-Torgay natural reserve are one and largest wetlands of Kazakhstan (area of 348 thousand hectares). On lakes tens and hundreds thousands birds stop during migrations on the West Asian migratory way. Here in large quantities many hy-drophilic species nest. The monitoring of bird s which was according to plan carried out in Irgiz-Turgay state natural reserve in 2008-2013, confirmed a high specific variety of birds as a whole in the reserve territory, and on lake system of the lower rivers. The global importance of wetlands of this zone in maintenance of migration of birds on flight, nesting, fodder stops and a molt causes recognition them as wetlands of international importance.
Keywords: wetland; hydrophilic; birds; migration; avifauna.